Gegenlicht : German Art from the George Economou Collection. - Buchhart, Dieter; Ozerkov, Dimitri; The State Hermitage Museum, St. Petersburg (St. Petersburg : The State Hermitage Museum, 2013)
Dix, Otto ; Schad, Christian ; Gramatté, Walter ; Felixmüller, Conrad ; Grosz, George ; Schlichter, Rudolf ; Baselitz, Georg ; Kirchner, Ernst Ludwig ; Heckel, Erich ; Macke, August ; Pechstein, Max Hermann ; Rauch, Neo ; Kiefer, Anselm
The State Hermitage Museum, Saint Petersburg, 24 May 2013 - 19 January 2014
kunstcatalogus
Keywords: Duitsland